2012
DOI: 10.1186/gb-2012-13-11-178
|View full text |Cite
|
Sign up to set email alerts
|

Why rodent pseudogenes refuse to retire

Abstract: A new study in this issue of Genome Biology sheds light on why some pseudogenes persist in rodent, and other mammalian, genomes.Please see related Research article by Marques et al http://genomebiology.com/2012/13/11/R102

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
(16 reference statements)
1
1
0
Order By: Relevance
“…We found there were one brachypodium relic, two rice relics and two sorghum relics encode different microRNA response elements and could be a plausible target for corresponding microRNAs, implying that they might become ceRNAs and thereby function as microRNA decoys [ 27 , 28 ]. Consistent with the hypothesis [ 4 , 26 , 29 ], we found there were protein-coding genes harbouring the same microRNA response elements in three prime untranslated region and expressing with positive correlation for each of these relics (Table 2 ). Further check showed that there were no out-paralog relationships between these relics and protein-coding genes, thus the sharing of the same microRNA response element is not due to the homology between them, further suggesting the possible ceRNA roles for these transcribed relics.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…We found there were one brachypodium relic, two rice relics and two sorghum relics encode different microRNA response elements and could be a plausible target for corresponding microRNAs, implying that they might become ceRNAs and thereby function as microRNA decoys [ 27 , 28 ]. Consistent with the hypothesis [ 4 , 26 , 29 ], we found there were protein-coding genes harbouring the same microRNA response elements in three prime untranslated region and expressing with positive correlation for each of these relics (Table 2 ). Further check showed that there were no out-paralog relationships between these relics and protein-coding genes, thus the sharing of the same microRNA response element is not due to the homology between them, further suggesting the possible ceRNA roles for these transcribed relics.…”
Section: Resultssupporting
confidence: 90%
“…It has been reported that transcripts losing coding potential could function as ceRNAs in rodents [ 4 , 26 ]. We found there were one brachypodium relic, two rice relics and two sorghum relics encode different microRNA response elements and could be a plausible target for corresponding microRNAs, implying that they might become ceRNAs and thereby function as microRNA decoys [ 27 , 28 ].…”
Section: Resultsmentioning
confidence: 99%